1991
DOI: 10.1161/01.hyp.17.5.593
|View full text |Cite
|
Sign up to set email alerts
|

Raynaud's phenomenon. An update.

Abstract: The pathogenesis of primary Raynaud's phenomenon remains an enigma. Most evidence favors a local abnormality in the digital arteries as opposed to an increased activity of the sympathetic nervous system. The local fault may involve the a^-adrenergic receptors, which are most important in reflex sympathetic vasoconstriction. Cooling blood vessels increase the sensitivity of o>2-adrenergic receptors, increased levels of a^-adrenergic receptors are present in primary Raynaud's disease, and patients show an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 78 publications
0
23
0
Order By: Relevance
“…Skin temperature differences between the center of palm and the coolest finger and between the center of the foot dorsum and the first toe was significantly bigger in RP patients than in controls, irrespective of RP symptom involving either hands or feet. RP is characterized by recurrent episodes of discoloration affecting the fingers and toes (10). According to a study of systemic sclerosis by La Montagna et al about 90% of patients were presented with features of RP in the feet (11) in contrast to 44% of the patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Skin temperature differences between the center of palm and the coolest finger and between the center of the foot dorsum and the first toe was significantly bigger in RP patients than in controls, irrespective of RP symptom involving either hands or feet. RP is characterized by recurrent episodes of discoloration affecting the fingers and toes (10). According to a study of systemic sclerosis by La Montagna et al about 90% of patients were presented with features of RP in the feet (11) in contrast to 44% of the patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Several decades later, Thomas Lewis suggested that the vasospasm was caused by some factor that is local to the blood vessels [2]. Current thinking often combines these two hypotheses suggesting that vasospasm occurs in those people in whom neurally or hormonally mediated vasoconstriction is potentiated by the action of a locally released substance or substances (see [1,3]). Rather surprisingly, the idea that vasospasm can be evoked by emotional stress has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…3 The presence of these abnormalities may aid in early diagnosis of these disorders and in the differential diagnosis of primary Raynaud phenomenon (RP) from RP due to scleroderma and MCTD. 2,3,[6][7][8][9] The instruments used to observe capillaries in the living skin have ranged from a magnifying glass to microscopes of various designs and magnifying power. 2,4,7,10 A total magnification of ϫ12 to ϫ14 offers a wide field of observation and a perception of depth, the best conditions for evaluating the overall pattern of the capillary bed, both normal and abnormal.…”
mentioning
confidence: 99%